Deposition and characterization of silver nano-films by a novel solid liquid interface reaction technique (SLIRT) - Godbole, P. D.; Mitra, A.; Pasricha, R.; Mandale, A. B.; Patil, K. R. (Materials Letters, 2005)
Solid-liquid interface reaction technique (SLIRT) is used to deposit silver film on glass substrate. The solid film of silver nitrate is formed by modified spin coating method. This film is subsequently processed by dipping it in a reducing solution so as to initiate a reaction at the interface and ultimately transform it to totally silver film. In situ transformation of silver nitrate to silver is studied with respect to time spectrophotometrically. The characterization of silver film is done by various physicochemical techniques namely XRD, XPS, ED, TEM and UV visible spectroscopy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Nano-Particles; solid-liquid interface reaction; thin film

Glycerol mediated low temperature synthesis of nickel nanoparticles by solution reduction method - Singh, Kalpana; Kate, Kunal H.; Chilukuri, V. V. Satayanarayana; Khanna, P. K. (Journal of Nanoscience and Nanotechnology, 2011)
Phase pure Nickel nano-particles were synthesized by in-situ generation of nickel hydrazine hydrate complex (Ni-HH) followed by its decomposition in an alkaline glycerol medium. The synthesis can be performed in an open beaker with or without the use of surface protective reagents. By using the present method, Ni nano-particles can be prepared in large scale. The black nano-powders so-obtained were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infra-red (FTIR) spectroscopy and thermal analysis (TGA). XRD and SAED analysis revealed that the synthesized particles were pure crystalline nickel with FCC structure.
Keywords: Chemical Reduction; Nano-Particles; synthesis; Transition Metal; XRD